Green synthesis of gold nanoparticles using Artemisia dracunculus extract: control of the shape and size by varying synthesis conditions - Wacławek, Stanisław; Gončuková, Zuzanna; Adach, Kinga; Fijałkowski, Mateusz; Černík, Miroslav (Environmental science and pollution research international, 2018)
In this study, selective green synthesis of gold nanoparticles (nAu) with the use of Tarragon extract (Artemisia dracunculus) was investigated. Characterization of the synthetized nAu was carried out using several techniques including: UV-Vis, SEM, zeta potential analysis, DLS, and ATR-FTIR. Based on measurements of Tarragon extract by HPLC-MS, significant chemical substances participating as reducing and stabilizing agents were identified. FTIR confirmed typical functional groups that could be found in these acids on the nAu surface, such as O-H, C=O and C-O. The effects of various parameters (concentration of Tarragon extract, Au precursor, and initial pH of the synthesis) on the shape and size of the nanoparticles have been investigated. UV-Vis and SEM confirmed the formation of nAu at various concentrations of the extract and Au precursor and showed correlation between the added extract concentration and shift in maximal absorbance towards higher frequencies, indicating the formation of smaller nanoplates. Zeta potential determined at various pH levels revealed that its value decreased with pH, but for all experiments in the pH range of 2.8 to 5.0, the value is below - 30 mV, an absolute value high enough for long-term nAu stability. In order to evaluate nAu catalytic activity, the reduction of 4-nitrophenol to 4-aminophenol by sodium borohydride was used as a model system. The reaction takes place 1.5 times faster on Au-triangles than on Au-spherical NPs.
Keywords: Green Chemistry Technology; aminofenoly; Gold nanoparticles; kovové nanočástice; Catalysis; velikost částic; Hydrogen-Ion Concentration; katalýza; Microscopy, Electron, Scanning; Particle Size; Tandem Mass Spectrometry; rostlinné extrakty; zlato; vysokoúčinná kapalinová chromatografie; nitrofenoly; Artemisia; mikroskopie elektronová rastrovací; Selective synthesis; Spectroscopy, Fourier Transform Infrared; spektrofotometrie ultrafialová; Metal Nanoparticles; Aminophenols; pelyněk; Chromatography, High Pressure Liquid; spektroskopie infračervená s Fourierovou transformací; 4-Nitrophenol reduction; tandemová hmotnostní spektrometrie; Spectrophotometry, Ultraviolet; technologie zelené chemie; Plant Extracts; Green synthesis; Borohydrides; Gold; borohydridy; Remediation; Nitrophenols; koncentrace vodíkových iontů